Private organisations in global politics - Ronit, Karsten; Schneider, Volker, 1952- (Routledge/ECPR studies in European political science, 2000)
Private Organisation in Global Politics is a groundbreaking study which brings together a broad range of case-studies to examine the role and character of private organisations in the process of political globalization. Focusing on areas such as human rights organisations, the international women's movement and the combating of disease, the panel of expert contributors investigate the function of these in relation to governance in the globalizing world.